Students’Perspectives toward the Impact of Using AI-Driven Tools in Academic Writing The Case study of Master 02 Students of English At Mohamed Cherif Messaadia at Souk Ahrass University - Douaa AMARNIA (My University, 2025)
Abstract This study aims to explore Master’s students’ perspectives on the impact of AI-driven tools in academic writing, and to examine university teachers' attitudes toward their integration into academic practice. The central issue addressed in this research is the increasing use of AI tools in academic settings, which has raised pedagogical and ethical concerns regarding students’ development and academic performance. To achieve this aim, a mixed-methods approach was employed, combining both quantitative and qualitative data. A questionnaire was administered to 34 Master’s students to gather measurable data about their familiarity with, usage patterns of, and attitudes toward AI tools. Additionally, semi-structured interviews were conducted with 12 teachers from the Department of English to gain in-depth insights into their experiences, concerns, and recommendations. The findings reveal that most students recognize the benefits of AI tools in improving grammar, clarity, and referencing, although many also highlight the need for guidance on ethical usage. Teachers acknowledged the potential advantages of these tools but expressed concerns about their impact on students' critical thinking and academic integrity. Both groups agreed on the importance of promoting the responsible and informed use of AI in academic writing. The study recommends the integration of formal training on AI tools into academic curricula and encourages the development of institutional guidelines to ensure ethical practices and balanced usage. -------------------- الملخص تهدف هذه الدراسة إلى استكشاف تصورات طلاب الماجستير حول تأثير أدوات الذكاء الاصطناعي في الكتابة الأكاديمية، وكذلك دراسة اتجاهات أساتذة الجامعات تجاه دمجهم في الممارسات التربوية. تتعلق القضية المركزية التي تم تناولها بالاستخدام المتزايد لهذه الأدوات في الأوساط الأكاديمية ، مما يثير أسئلة تربوية وأخلاقية حول تطوير الطلاب وأدائهم. للقيام بذلك ، تم اعتماد طريقة مختلطة تجمع بين البيانات الكمية والنوعية. تم توزيع استبيان على 34 طالبا من طلاب الماجستير لجمع البيانات حول معرفتهم وعاداتهم التعريفية وآرائهم. بالإضافة إلى ذلك ، أجريت مقابلات شبه منظمة مع 12 أستاذا جامعيا لجمع وجهات نظر متعمقة حول تجاربهم ومخاوفهم وتوصياتهم. تظهر النتائج أن غالبية الطلاب يدركون فوائد أدوات الذكاء الاصطناعي لتحسين القواعد والوضوح وإدارة المراجع ، مع تسليط الضوء أيضا على الحاجة إلى التوجيه الأخلاقي. من ناحية أخرى ، يدرك المعلمون فائدتها ، لكنهم يعبرون عن مخاوفهم بشأن تأثيرها على التفكير النقدي والصدق الأكاديمي. تتفق كلتا المجموعتين على الحاجة إلى تعزيز الاستخدام المسؤول والمستنير لمنظمة الذكاء الاصطناعي في الكتابة الأكاديمية. توصي الدراسة بإدماج التدريب الرسمي على أدوات الذكاء الاصطناعي في المناهج الجامعية بالإضافة إلى تطوير مبادئ توجيهية مؤسسية لضمان الاستخدام الأخلاقي والمتوازن. -------------------------- Résumé Cette étude vise à explorer les perceptions des étudiants en Master sur l’impact des outils d’IA dans la rédaction académique, ainsi qu’à examiner les attitudes des enseignants universitaires vis-à-vis de leur intégration dans les pratiquespédagogiques. Le problème central abordé concerne l’usage croissant de ces outils dans les milieux académiques, suscitant des questions pédagogiques et éthiques quant au développement et aux performances des étudiants. Pour ce faire, une méthode mixte a été adoptée, combinant des données quantitatives et qualitatives. Un questionnaire a été distribué à 34 étudiants de Master pourrecueillir des données sur leur familiarité, leurs habitudes d’utilisation et leursopinions. Par ailleurs, des entretiens semi-directifs ont été menés auprès de 12enseignants universitaires afin de recueillir des perspectives approfondies sur leurs expériences, inquiétudes et recommandations. Les résultats montrent que la majorité des étudiants reconnaissent les avantages des outils d’IA pour améliorer la grammaire, la clarté et la gestion des références, tout en soulignant le besoin d’un encadrement éthique. Les enseignants, quant à eux, reconnaissent leur utilité, mais expriment des inquiétudes concernant leur impact sur la pensée critique et l’honnêteté académique. Les deux groupes s’accordent sur lanécessité de promouvoir un usage responsable et éclairé de l’IA dans la rédactionacadémique. L’étude recommande l’intégration d’une formation formelle sur les outils d’IA dans les programmes universitaires ainsi que l’élaboration de directives institutionnelles afin d’assurer un usage éthique et équilibré
Keywords: AI tools; Artificial intelligence; academic writing; perspectives; academic integrity; academic performance; أدوات الذكاء الاصطناعي،الذكاء الاصطناعي،الكتابة الأكاديمية، وجهات النظر ، النزاهة الأكاديمية، الاداء الأكاديمي .; outils d’intelligence artificielle; intelligence artificielle; écriture académique; intégrité académique; performance académique